EKSISTENSI PONDOK PESANTREN SALAFI - Prasanti, Ditha (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 13 No 1 (2017), 2017)
This paper discusses Pesantren Miftahul Huda and factors that cause this salafi pesantren chose to maintain its salafiyyah in this modern era. This research used qualitative approach with a method of case study. The result of this research shows that the factors that make the salafi pesantren Miftahul Huda exists in this modern era are: first, the belief in the teachings of Islam spread by Walisongo (Nine Saints) that the first Islamic education in the land of Java is a salafi pesantren; Second, the mandate of the ancestors of who had pioneered the pesantren the  salafi pesantren must exist until the end of time; Thirdly, Pesantren Miftahul Huda as salafi pesantren which was first established in Tasikmalaya in 1967 has a good management in establishing the strategy of developing salafi pesantren.